A bibliometric analysis of marketing for children: Future research agenda - Ekasasi, Sri Rejeki; Supardin, Lalu; Rinaldi, Rinaldi; Hasan, Israk Fabian (Asian Management and Business Review, 2026)
In recent decades, marketing research has developed rapidly, yet studies specifically focusing on marketing for children remain limited. Based on the Scopus database, children-oriented marketing is often overlooked, despite its potential as a long-term strategy to build brand loyalty from an early age until adulthood. Many studies view marketing for children as a crucial approach to sustain lifelong customer relationships. This study aims to conduct a bibliometric analysis of marketing for children by reviewing empirical studies published in Scopus, offering a new perspective on this underexplored topic, particularly in Indonesia. A systematic literature review (SLR) was employed, using titles, abstracts, and keywords from Scopus within a defined timeframe. VOSviewer software was applied to map research trends, author collaborations, and frequently used keywords. Results indicate that research on children’s marketing continues to evolve, with key themes including its impact on children’s consumption behavior, the role of regulations, and technological influences in shaping strategies. Prior studies highlight children’s vulnerability to digital marketing, particularly their difficulty distinguishing between advertising and organic content. This suggests a need for further exploration of the long-term effects of marketing practices on children and the effectiveness of regulatory measures across countries. The findings provide practical insights for marketers, policymakers, and academics in creating more responsible and ethical marketing strategies in the digital age. Research on children’s marketing strategies remains scarce, especially in Indonesia. This study contributes a fresh perspective to bridge existing gaps and encourages more comprehensive exploration of the field.